2008
DOI: 10.1186/1477-7827-6-65
|View full text |Cite
|
Sign up to set email alerts
|

Bovine endometrial stromal cells display osteogenic properties

Abstract: The endometrium is central to mammalian fertility. The endometrial stromal cells are very dynamic, growing and differentiating throughout the estrous cycle and pregnancy. In humans, stromal cells appear to have progenitor or stem cell capabilities and the cells can even differentiate into bone. It is not clear whether bovine endometrial stromal cells exhibit a similar phenotypic plasticity. So, the present study tested the hypothesis that bovine endometrial stromal cells could be differentiated along an osteog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 38 publications
1
52
0
Order By: Relevance
“…The uterine cells differentiated in vitro, under proper conditions, into three mesenchymal lineages: adipogenic, chondrogenic, and osteogenic. These results suggest the wide plasticity of phenotype of bovine uterine cells and the presence of undifferentiated stem cells in the bovine uterus, thus we confirmed and extended the results obtained by Donofrio et al (2008).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The uterine cells differentiated in vitro, under proper conditions, into three mesenchymal lineages: adipogenic, chondrogenic, and osteogenic. These results suggest the wide plasticity of phenotype of bovine uterine cells and the presence of undifferentiated stem cells in the bovine uterus, thus we confirmed and extended the results obtained by Donofrio et al (2008).…”
Section: Discussionsupporting
confidence: 80%
“…To our knowledge, this is the first study that concerned the identification of stem cell markers in the bovine uterus relative to animals' age, uterine horn side, and type of uterine cells. Donofrio et al (2008) were the first ones to isolate from the bovine uterus a population of endometrial stromal cells that displayed the capacity to differentiate in vitro into bone tissue. That study suggests that in the bovine endometrium exists a population of cells possessing wide plasticity of phenotype, and that they may differentiate into distinct mesenchymal cell lineages, which are characteristics of MSc (Donofrio et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is great commonality between uterine-and bone-signaling pathways, and activation of SMO in the uterus leads to a chondrocytic phenotype. Furthermore, cultured endometrial stromal cells, both human and bovine, have been shown to exhibit chondrocytic/osteogenic properties, which may occur as a result of a perturbation in endometrial Hh signaling [43,44]. In addition to demonstrating that Hh activation results in the induction of genes involved in chondrocyte proliferation and differentiation, these data also suggest that SMO activation may be affecting a progenitor cell population as the uterine stromal cells exhibit an altered differentiation profile; additional studies need to be conducted to explore this further.…”
Section: Discussionmentioning
confidence: 99%
“…58 Cabezas et al 59 studied the uteri of healthy Holstein cows at the beginning of the oestrous cycle luteal phase (days 1-5 post-ovulation) and during the luteal phase (between days 13 and 18 post-ovulation) to search for stem cells. These authors were able to identify the expression of markers for embryonic stem cells (OCT4 and SOX2) and MSCs (STAT3, CD44 and c-KIT) in the cow endometria during both periods of the oestrous cycle luteal phase.…”
Section: Endometrial Mscs In Cowsmentioning
confidence: 99%